Exports and sectoral financial dependence: evidence on French firms during the great global crisis - Jean-Charles Bricongne; Lionel Fontagné; Guillaume Gaulier; Daria Taglioni; Vincent Vicard (European Central Bank (ECB), 2010)
The unprecedented drop in international trade during the last quarter of 2008 and the first quarter of 2009 has mainly been analysed at the macroeconomic or sectoral level. However, exporters who are heterogeneous in terms of productivity, size or external financial dependence should be heterogeneously affected by the crisis. This issue is examined in this paper by using data on monthly exports at the product and destination level for some 100,000 individual French exporters, up to 2009M4. We show that the drop in French exports is mainly due to the intensive margin of large exporters. Small and large exporters are evenly affected when sectoral and geographical specialisations are controlled for. Lastly, exporters (small and large) in sectors structurally more dependent on external finance are the most affected by the crisis.
Keywords: F02; F10; G01; 330; financial crisis; firms' heterogeneity; intensive and extensive margins; international trade; Finanzkrise; Internationale Wirtschaftsbeziehungen; Exportwirtschaft; Branche; Frankreich